2020
DOI: 10.1097/wnf.0000000000000400
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Piribedil Relative to Pramipexole for the Treatment of Early Parkinson Disease: A Systematic Literature Review and Network Meta-Analysis

Abstract: Objectives Patients with early Parkinson disease (PD) frequently defer initiation of levodopa treatment to minimize long-term complications. Nonergoline dopamine agonists, such as pramipexole and piribedil, are frequent first-line therapies for early PD patients, yet limited head-to-head randomized controlled trial (RCT) evidence exists for dopamine agonists in this population. We therefore conducted a systematic literature review and network meta-analysis. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…Additionally, for interclass comparison of efficacy, consistent with our research, a Cochrane meta‐analysis including 44 trials involving 8436 participants has also revealed that as adjuvant treatments to levodopa therapy, dopamine agonists were more efficacious in PD patients with UPDRS score improvements, off‐time, and levodopa dose reduction than MAOBIs and COMTIs 14 . While for the intraclass comparison between dopamine agonists, several network meta‐analyses have reported that pramipexole and piribedil had no significant differences in improving non‐motor symptoms with similar UPDRS II and UPDRS III scores in early Parkinson's disease, 26,27 which was not in line with our study. Meanwhile, pramipexole was likely superior to selegiline in effectiveness as monotherapy, which turned out to be the opposite when used in combination with levodopa 28 .…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, for interclass comparison of efficacy, consistent with our research, a Cochrane meta‐analysis including 44 trials involving 8436 participants has also revealed that as adjuvant treatments to levodopa therapy, dopamine agonists were more efficacious in PD patients with UPDRS score improvements, off‐time, and levodopa dose reduction than MAOBIs and COMTIs 14 . While for the intraclass comparison between dopamine agonists, several network meta‐analyses have reported that pramipexole and piribedil had no significant differences in improving non‐motor symptoms with similar UPDRS II and UPDRS III scores in early Parkinson's disease, 26,27 which was not in line with our study. Meanwhile, pramipexole was likely superior to selegiline in effectiveness as monotherapy, which turned out to be the opposite when used in combination with levodopa 28 .…”
Section: Discussionsupporting
confidence: 81%
“…The introduction of active fragments is a common strategy for drug development. Similar in structure to terazosin, Piribedil also has a pyrimidine-2-piperazine group and has been shown to exert anti-PD effects by affecting energy metabolism ( Chen et al, 2020 ). We developed compound 7c by introducing its unique piperonyl group.…”
Section: Resultsmentioning
confidence: 99%
“…When compared to rasagiline, fewer systematic reviews and meta-analyses are available for pramipexole and PD patients. A recent systematic review by Chen et al [ 44 ] identified six trials that compared the efficacy of pramipexole versus placebo in patients with early PD as defined by a Hoehn and Yahr score of <3. This study showed no benefit of pramipexole at 22 to 30 weeks after initiation of therapy on the change in either UPDRS Part II (mean difference = 0.02, 95% confidence interval: −1.15 to 1.12) or Part III (mean difference = 0.32, 95% confidence interval: −8.22 to 7.95) scores.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed no benefit of pramipexole at 22 to 30 weeks after initiation of therapy on the change in either UPDRS Part II (mean difference = 0.02, 95% confidence interval: −1.15 to 1.12) or Part III (mean difference = 0.32, 95% confidence interval: −8.22 to 7.95) scores. Evaluation of safety data showed that pramipexole demonstrated significantly higher event rates for nausea than placebo [ 44 ]. A systematic review by Ji et al [ 45 ] including 23 randomized clinical trials showed pramipexole was effective in lowering the Hamilton Depression Rating Scale (HAM-D) score in PD patients with anxiety or depression.…”
Section: Discussionmentioning
confidence: 99%